Yi dai zong shi = The Grandmaster [videorecording (DVD)] - Wong, Kar-wai, 1958-; Zou, Jingzhi; Xu, Haofeng; Leung, Tony Chiu Wai, 1962-; Zhang, Ziyi, 1979-; Zhang, Zhen, 1976 October 14-; Song, Hye-gyo, 1982-; Zhao, Benshan, 1958-; Xiaoshenyang, 1981-; Zhang, Jin, 1974 May-; Le Sourd, Philippe; Umebayashi, Shigeru, 1951-; et al. (Anchor Bay Entertainment, 2014)
Watch an epic action feature inspired by the life and times of the legendary kung fu master, Ip Man, who mentored Bruce Lee. The story spans the tumultuous Republican era that followed the fall of China's last dynasty, a time of chaos, division, and war that was also the golden age of Chinese martial arts.